Contrasting Dose-Effects of Multi-glycoside of Tripterygium wilfordii HOOK. f. on Glomerular Inflammation and Hepatic Damage in Two Types of Anti-Thy1.1 Glomerulonephritis - Yi-Gang Wan; Qing Zhao; Wei Sun; Hui-Lan Zhang; Min Li; Qing-Xue Wei; Wei Wu; Li-Jun Yue; Qing Wang (Elsevier, 2012)
Multi-glycoside, one of the extracted compounds from Tripterygium wilfordii HOOK. f. (GTW), has been shown to be clinically effective in suppressing glomerular inflammation in chronic kidney disease. However, its clinical application is often limited by its cytotoxic actions on the liver. This study was performed to contrast the dose-effects of GTW on glomerular inflammation and hepatic damage in two types of anti-Thy1.1 glomerulonephritis (GN). Rats with acute or chronic anti-Thy1.1 GN were either left untreated (the Vehicle group) or treated with a high or low dose of GTW and sacrificed on day 7 or day 45. GTW was administrated 3 days before or at the same time as the antibody injection and lasted until sacrifice. GTW at high dose ameliorated glomerular macrophage accumulation, mesangial proliferation, proteinuria, and interleukin-2 expression in the acute anti-Thy1.1 GN model, but caused structural and functional lesions in the liver. In contrast, GTW at low dose improved activated macrophage and T lymphocyte infiltration, mesangial injury, proteinuria, and interleukin-2 and interferon-γ expressions without hepatic toxicity in the chronic model of GN induced by anti-Thy1.1 antibody. In conclusion, GTW at low dose not only effectively inhibits glomerular inflammation but also avoids severe injuries to the liver. Keywords:: anti-Thy1.1 glomerulonephritis, multi-glycoside of Tripterygium wilfordii HOOK. f. (GTW), macrophage, T lymphocyte, cytokine